ESTUDO DE UM SISTEMA DE SUSPENSÃO TRASEIRA PARA O PROTÓTIPO BAJA - BONFADA, ANDERSON R.; KAFKA, DAVID; ABENTROTH, FERNANDO H.; GILAPA, GENARO M. M.; BARBIERI, JOAO R. P.; STAMM, JOÃO G.; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; BATAGLIN, MARCELO; BENATTI, MATEUS; DECIAN, MAXUEL R. B.; et al. (Salão do Conhecimento, 2013)
Resumo